2020
DOI: 10.1097/mou.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

New paradigms in the management of recurrent urinary tract infections

Abstract: Purpose of review Recurrent urinary tract infections (rUTIs) represent a large burden on the healthcare system. Recent guidelines from the AUA/CUA/SUFU and advancements in the field reflect a paradigm shift for clinician and patients, steering away from empiric antibiotic therapy towards judicious antibiotic use. Recent findings Antibiotic stewardship, including increasing awareness of the collateral damage of antibiotics and the risks of bacterial resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…The current paradigm for antibiotic stewardship in the treatment of UTI prioritizes the use of first-line therapies such as trimethoprim and nitrofurantoin [ 5 ]. However, these agents are often ineffective against ESBL-producing E. coli .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current paradigm for antibiotic stewardship in the treatment of UTI prioritizes the use of first-line therapies such as trimethoprim and nitrofurantoin [ 5 ]. However, these agents are often ineffective against ESBL-producing E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Studies published in 2014 and 2016 reported similar findings [ 21 , 22 ]. Antimicrobial stewardship programs have refined the management of asymptomatic bacteriuria and UTI [ 5 ]. This approach may have reduced the impact of antimicrobial therapy on the development of antibiotic resistance in GNB, including E. coli [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Однако, оценивая эпидемиологию ИНМП, следует учитывать два важных фактора. Первый: ИНМП занимают второе по частоте место в мире после острых респираторных инфекций, а самыми распространенными среди них являются острый и хронический цистит [9,10]. Второй: флора в придаточных железах уретры часто соответствует влагалищной, что указывает на возможные пути проникновения патогенных микроорганизмов и значение патологий органов малого таза в воспалении структур, рассматриваемых в данном обзоре [8].…”
Section: эпидемиологияunclassified
“…ИМВП занимают 2-е по частоте место после острых респираторных инфекций, а самыми частыми среди них являются инфекции нижних отделов МВП -острый и рецидивирующий цистит. По весьма консервативной оценке, распространенность острого цистита (ОЦ) у взрослых женщин составляет около 11% [5], следовательно, в РФ следует ожидать примерно 8 млн ежегодных случаев, и это без учета рецидивирующих и хронических инфекций. В отличие от респираторных инфекций, ОЦ является бактериальной патологией, а значит, требует обязательного назначения антибактериальной терапии.…”
Section: актуальностьunclassified